The Green River of Kentucky - Crocker, Helen Bartter (Kentucky Bicentennial bookshelf., 2009)
Cutting a wide east-west swath from the Appalachian foothills to the heart of the western Kentucky coalfields, the Green River valley extends from below the Tennessee border in the south to the Ohio River in the north. The Green River of Kentucky presents a picture of the unity and diversity of the people living in the Green River valley. Helen Bartter Crocker finds that each generation of its people approached the river in a distinctive way. Early settlers used the river simply as it was -- crooked and narrow with an unpredictable water flow, and navigable only under high-water conditions. Th.